Update on the prevention and treatment of tumor lysis syndrome. Issue 1 (February 2019) - Sury, Krishna
Tumor lysis syndrome is a constellation of metabolic derangements seen when tumor cells die and release their intracellular contents into the systemic circulation. Hyperkalemia, hyperphosphatemia, hypocalcemia, and hyperuricemia may lead to severe organ dysfunction and even death. Tumor lysis syndrome is classically considered a complication of successful cancer treatment, but it can also occur in untreated malignancies characterized by rapid proliferation. In this review, we cover the types of cancers and chemo- and immunotherapies associated with tumor lysis syndrome, the mechanisms by which severe metabolic derangements can develop, and the available treatments.